FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN SAFETY DRIVING PADA PENGEMUDI BUS EKONOMI TRAYEK SEMARANG – SURABAYA DI TERMINAL TERBOYO SEMARANG - Avendika Bagoes Paasetya; Bina Kurnaiwan; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Safety driving is an effective way to reduce the incidence of accidents due to driver inattention while driving. In Indonesia, the cause of most accidents are caused by human error, which reached 90%. Traffic accidents are one of the safety risks to the driver economi bus which lasts for 24 hours a day.This study aims to identify the factors of related safety driving on driver bus economic class route Semarang – Surabaya in Terboyo terminal Semarang. This type of research is analytic survey with cross sectional study. Subjects in this study is the economic driver of the bus route Semarang - Surabaya in “Terminal Terboyo” as key informants. The sample in this study included all economic bus driver route Surabaya - Semarang totaling 40 with different “PO”.Based on the results of the study, researchers concluded that the level of education is not associated premises driving safety, with α = 0.763, years of dealing with driving safety, with α = 0.003, attitudes related to driving safety, with α = 0.004, training driving safety related with driving safety, with α = 0.002, the rules relating to driving safety, with α = 0.003, vehicle conditions related to driving safety, with α = 0.003, the role of co-workers related to driving safety, with α = 0.004, knowledge related to driving safety, with a α = 0.004.Researchers suggested that the held improvement to vehicle tires that has begun to thin, repair sewers that have developed porous at the bottom, and repair speedometer that is not lit, providing training on the driver's safety driving.